Alpinia galanga or Lengkuas (Zingiberaceae): A Possible Treatment for COVID-19 - Arif Nur Muhammad Ansori (Institute of Medico-legal Publications Pvt Ltd, 2021)
Alpinia galanga (Zingiberaceae) or lengkuas is one type of herbal plant that is widely grown in SoutheastAsia. Various countries cultivate this medicinal plant, including Indonesia. This medicinal plant has a varietyof benefits and also be used as a treatment for many diseases. Although the lengkuas rhizome is the mostwidely used and studied part of the plant, the flower on the lengkuas can also provide additional advantages,such as antioxidant and antimicrobial properties. Therefore, this study aimed to demonstrate lengkuas for thefuture prospects against SARS-CoV-2. In summary, this study suggests that lengkuas might be useful as atreatment for COVID-19, although further studies could be conducted to confirm the results of computationalstudies.